A CLINICAL CASE OF ANKYLOSING SPONDYLITIS IN A PATIENT WITH DYSPLASTIC SCOLIOSIS - A. Hochenkova; Elena Belyaeva (Clinical Medicine and Pharmacology, 2026)
Damage to the musculoskeletal system is one of the most common manifestations of rheumatic diseases. However, the reason for its involvement in the pathological process may be other diseases or their combinations. Ankylosing spondylitis (AS) is one of the most difficult to diagnose causes of specific pain in the lower back. The causes of difficulties in diagnosing the disease are untimely treatment of patients for medical help, a low-symptomatic course of AS, insufficient knowledge of the diagnostic criteria of the disease by doctors, and the presence of other pathological conditions accompanied by back pain. The article presents a clinical case of ankylosing spondylitis in an HLA-B27 positive patient with a history of dysplastic scoliosis surgery.